Measuring market risk for financial assets with moderate tail fatness: the case of global government bond portfolios. Issue 3 (22nd January 2010) - Dimitrakopoulos, Dimitris; Spyrou, Spyros
The downside risk for fixed-income securities is typically smaller than that of other financial assets such as equities and commodities; therefore, market risk models selected for risk measurement for the latter assets may not be valid in the case of fixed-income securities which exhibit fundamentally different tail properties. This paper explores the issue of price risk measurement for bond markets by employing the methodologies of value at risk and expected shortfall for global government bond portfolios. Four popular VaR and ES methods (riskmetrics, historical simulation, Monte Carlo simulation, extreme value) are estimated for backtesting. The results indicate that the riskmetrics method appears to be the most successful method for specifying shortfall risk and bounded lower loss quintiles, even during periods of financial turmoil. This contradicts earlier findings from studies carried out for other financial assets according to which extreme value methods and filtered models dominate the traditional models.